Catalysts of Change for a Better Tomorrow: The New Age Social Impact Entrepreneurs of the 21st Century - Sreenivas Reddy, L.; Suryanarayana, A. (International Journal of Advances in Business and Management Research (IJABMR), 2025)
This conceptual paper examines the changing face of entrepreneurship in the 21st century, with a focus on the rising concept of social impact entrepreneurship and the implications of this theoretical model for contemporary disruptions of the status quo. The goal is to explore how these people and companies go beyond profit-focused business models, integrating purpose, inclusivity, and sustainability into the very fabric of what they do. Based on a multidisciplinary review of entrepreneurship theory, social innovation literature, and sustainability frameworks, the paper critically unpacks the strategic behaviours, motivation, and ecosystemic dynamics that drive the emergence of social impact entrepreneurs. The design of this study emanates from a theoretical analysis and integrative framework. It unpacks a few important constructs like mission-driven leadership, stakeholder engagement, and impact-oriented value creation, introducing the conceptual frame through which to appreciate their particular place in the global development conversation. Although the paper does not present empirical findings, it introduces conceptual novelty by identifying the evolving landscape of entrepreneurial intention and highlights the blurred distinctions between ethical capitalism and entrepreneurship. The results of this Paper are a typology for 21st-century social impact entrepreneurs and a conceptual framework that may be useful for future empirical research. Its lack of empiricism is that it now must be validated with case studies or cross-sector data. However, it is relevant for academia, policy, and practice because it can impact educational curricula, strategies for incubators, and inclusive policy measures. The Paper’s contribution lies in reconfiguring social entrepreneurs as dynamic actors of societal change, whose initiatives embody conjoint economic prospects and moral imagination.